PERAN INVESTASI SEKTOR UMKM DALAM MENINGKATKAN PERTUMBUHAN EKONOMI INDONESIA - Nur, Muh.; Ummah, Rahila Amanatul; Azizs, Abdul; Ladjin, Nurjanna; Suryati, Suryati (JURNAL LENTERA BISNIS, 2025)
This study aims to determine the role of investment in the MSME sector in increasing economic growth in Indonesia. This research approach collects data through a literature review, which involves reading literature from various sources including books, articles, journals, and reports using qualitative and deductive approaches. The results of this study indicate that investment in the MSME sector plays a strategic role in driving economic growth in Indonesia. Access to financing, business mentoring, and technical support enables MSMEs to increase production capacity, output quality, and business competitiveness. Macroeconomically, investment flows into the MSME sector contribute to increased output and Gross Domestic Product (GDP), expanded employment, and strengthened household incomes. It also encourages economic diversification through the development of various business sectors, thereby strengthening the national economic structure. Thus, investment in the MSME sector plays a crucial role in creating inclusive, stable, and sustainable economic growth.